Misfolding at the synapse: A role in amyotrophic lateral sclerosis pathogenesis? - Lum, Jeremy S.; Yerbury, Justin J. (Frontiers in Molecular Neuroscience, 2022)
A growing wave of evidence has placed the concept of protein homeostasis at the center of the pathogenesis of amyotrophic lateral sclerosis (ALS). This is due primarily to the presence of pathological transactive response DNA-binding protein (TDP-43), fused in sarcoma (FUS) or superoxide dismutase-1 (SOD1) inclusions within motor neurons of ALS postmortem tissue. However, the earliest pathological alterations associated with ALS occur to the structure and function of the synapse, prior to motor neuron loss. Recent evidence demonstrates the pathological accumulation of ALS-associated proteins (TDP-43, FUS, C9orf72-associated di-peptide repeats and SOD1) within the axo-synaptic compartment of motor neurons. In this review, we discuss this recent evidence and how axo-synaptic proteome dyshomeostasis may contribute to synaptic dysfunction in ALS.